TRANSFORMATION OF COGNITIVE PROCESSES UNDER THE INFLUENCE OF INFORMATION FLOWS (Global Conference on Medical and Health Sciences, 2026)
The article examines how intensive information flows in the digital environment transform human cognitive processes. Special attention is paid to attention, memory, perception, thinking, decision-making and deep reading. The paper argues that information flows do not simply increase the amount of available knowledge, but also change the mechanisms through which people select, process, store and interpret information. On the one hand, digital media expand access to knowledge, support fast search and stimulate new forms of distributed cognition. On the other hand, constant notifications, multitasking, fragmented reading and dependence on external memory may weaken concentration, critical reflection and long-term semantic understanding. The article concludes that the main task of modern education is not to reject information technologies, but to develop cognitive hygiene, media literacy and reflective thinking.
Keywords: information flow, cognition, attention, memory, digital environment, multitasking, critical thinking, cognitive transformation.